Answer: x={-7,-4}
Step-by-step explanation: Simplifying
x2 + 11x + 28 = 0
Reorder the terms:
28 + 11x + x2 = 0
Solving
28 + 11x + x2 = 0
Solving for variable 'x'.
Factor a trinomial.
(7 + x)(4 + x) = 0
Subproblem 1
Set the factor '(7 + x)' equal to zero and attempt to solve:
Simplifying
7 + x = 0
Solving
7 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-7' to each side of the equation.
7 + -7 + x = 0 + -7
Combine like terms: 7 + -7 = 0
0 + x = 0 + -7
x = 0 + -7
Combine like terms: 0 + -7 = -7
x = -7
Simplifying
x = -7
Subproblem 2
Set the factor '(4 + x)' equal to zero and attempt to solve:
Simplifying
4 + x = 0
Solving
4 + x = 0
Move all terms containing x to the left, all other terms to the right.
Add '-4' to each side of the equation.
4 + -4 + x = 0 + -4
Combine like terms: 4 + -4 = 0
0 + x = 0 + -4
x = 0 + -4
Combine like terms: 0 + -4 = -4
x = -4
Simplifying
x = -4
Solution
x = {-7, -4}